INFLUENCE OF ORGANIC ADDITIVES ON MULTIPLE SHOOT FORMATION OF MUSA (AA GROUP) ‘KLUAI NAM THAI’ IN VITRO - Kassanuk, Thanwamas; Selakorn, Orapin; Phasinam, Khongdet; Sutaphan, Sudarat (Life Sciences and Environment Journal, 2020)
‘Kluai Nam Thai’ (Musa AA group) are rare in Thailand and it is at risk of extinction because of environmental changes and human behavior. Hence, the plant tissue culture technique is used for propagation. The influence of organic additives on multiple shoot formation of Kluai Nam Thai in vitro was investigated. Shoot explants were cultured on MS medium supplemented with coconut water, pineapple juice and orange juice at a 200 mL/L concentration for four months. The experimental design was Completely Randomized Design (CRD). The results indicated that MS medium supplemented with 200 mL/L coconut water gave the highest average number of shoots 1.71 shoots/explant, the highest average shoot length 4.25 cm and the highest average number of leaf four leaves/explant which were significantly different (p≤0.01).